Neuropsychological assessment of Boucher-Neuhäuser syndrome: A case report. Issue 8 (17th November 2022) - Merolla, Stefano; Borella, Monica; Bassi, Francesca; Canonico, Francesco; Santilli, Ignazio Michele; Grassi, Maria Pia
Abstract: Objective: Boucher-Neuhäuser Syndrome (BNS) is a rare autosomal recessive disorder characterized by hypogonadotropic hypogonadism, spinocerebellar ataxia, and chorioretinal syndrome, and associated with a variant in the PNPLA6 gene . Although many reports have mentioned the presence of cognitive impairment, a neuropsychological assessment of a BNS case has never been published. Here, we provide a detailed description of a young adult patient with BNS who has a homozygous pathogenic variant in the PNPLA6 gene. Method: A 21-year-old man with progressive ataxia and a history of hypogonadotropic hypogonadism and chorioretinal dystrophy was diagnosed with BNS. A comprehensive cognitive evaluation was performed, requiring the ad hoc selection and adaption of neuropsychological tests to overcome visual and motor impairments that characterize this syndrome. Results: The patient presented an intact global cognitive profile with selective executive dysfunction and mild verbal reasoning dysfunction. In particular, attentional-inhibitory control, working memory, and set switching were impaired, and inadequate development of conceptual knowledge and abstract reasoning was observed. Conclusions: This is the first report of an explicitly documented comprehensive neuropsychological assessment in a patient with BNS. The battery we composed is an example of a methodology that can be used to conduct a detailed cognitive examination without being penalized for physical impairment. Further studies are needed to define the typical cognitive features that characterize BNS and possibly identify its cognitive phenotype(s).